The origin and evolution of cell types - Arendt, Detlev; Musser, Jacob M.; Baker, Clare V. H.; Bergman, Aviv; Cepko, Connie; Erwin, Douglas H.; Pavlicev, Mihaela; Schlosser, Gerhard; Widder, Stefanie; Laubichler, Manfred D.; Wagner, Günter P. (Nature reviews. Genetics, 2016)
A new evolutionary definition of cell types is presented. Cell types are evolutionary units defined by common descent rather than phenotypic similarity, and characterized by their ability to evolve gene expression programmes independently of each other.The evolutionary diversification of cell types is driven by genomic individuation, which increases the capacity of sister cell types to establish and maintain distinct gene expression programmes.Core regulatory complexes (CoRCs) of terminal selectors determine cell type identity. CoRCs are the molecular agents that enable cell type-specific gene expression.Apomeres are new cellular modules or variants of modules in incipient sister cell types that implement cell type-specific structure and functions.Concerted evolution is characteristic for related cell types that share some genomic information, such as genes or shared enhancers.The evolutionary lineage of cell type individuation is different from the developmental lineage. Serial sister cell types that develop from distinct developmental regions are closely related in evolution but differ in developmental lineage.
Gesehen am 18.08.2020